Peningkatan Skill Manajemen Keuangan Dan Pencatatan Keuangan UMKM Dengan Aplikasi Buku Warung - Efni Cerya; Gilang Oritaliano Putra; Yuriza Maulidina (Universitas Negeri Padang, 2022)
Micro, Small and Medium Enterprises (MSMEs) is a driving force for the national economy that is able to increase national income and create jobs so as to increase welfare and reduce poverty. The problem currently faced in West Sumatra is that several Micro, Small and Medium Enterprises in West Sumatra cannot develop and some do not last long. This is caused by several factors, one of which is financial management. The shop book is an application that is used as a financial record and management of credit transactions for micro businesses. Buku warung is an application that can be used via a smartphone where everyone today has a smartphone in hand.